2018
DOI: 10.18186/thermal.439057
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Flow and Heat Transfer in Communicating Converging and Diverging Channels

Abstract: Fluid flow and heat transfer in communicating converging and diverging channel has been numerically investigated. Channels are assumed to be at constant wall temperature and the flow is assumed to be steady state and incompressible. Since the flow and temperature fields to repeat periodically after a certain developing length, periodic boundary conditions are used for the calculations. Finite volume method is used to solve the governing differential equations numerically. Computations are performed for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…When the holder plate is in line with the symmetry line of the channel, fluid flow has similar hydrodynamic behavior at both sides of the plate. Finally, the studies of Erdinc and Yilmaz [21] is proposed to compare the present results with the results for the case of converging and diverging channels.…”
Section: Discussionmentioning
confidence: 91%
“…When the holder plate is in line with the symmetry line of the channel, fluid flow has similar hydrodynamic behavior at both sides of the plate. Finally, the studies of Erdinc and Yilmaz [21] is proposed to compare the present results with the results for the case of converging and diverging channels.…”
Section: Discussionmentioning
confidence: 91%
“…Active control techniques are instrumental, such as suction [10] and blowing [1,4,5,11], and reactive in the form of rotating cylinders [12]. The various studies on the flow through nozzle and diffuser are available in the literature [19][20][21].…”
Section: Figure 1 Suddenly Expanded Flow Field [1]mentioning
confidence: 99%
“…Laksmana and Rajesh 12 considered the laminar HTP of nanofluid in converging pipes using FVM and their results corroborate the previous studies of Al‐sammarraie et al 8 Toghraie et al 13 examined the effect of wavelength on the HTP of water flowing in a converging‐diverging channel. The authors reported that an increase in wavelength reduces the Nu. Erdinç and Yılmaz 14 investigated laminar HTP of incompressible fluid flowing in communicating diverging and converging channels using FVM. The work focused on the effect of plate angle and Re on Nu and dP. The authors reported an increment in values of Nu and dP relative to the straight channel.…”
Section: Introductionmentioning
confidence: 99%